Legal Review of The Phenomenon of Naturalization of Foreign Players for The Indonesian National Football Team - Reyman Dhani; Adam Satria Pratama; Aryo Putra Pangestu; Zakka Asvi Auful Shohi M (Indonesian Journal of Sports Law, 2024)
Football is a sport that is favored by various ages, both young and old. There are so many legal patterns that exist in the sport of football. One of the is the phenomenon of naturalization, which means that a process carried out for foreigners to obtain Indonesian citizenship status. This is done by a football club to improve team performance, as well as adding diversification of a football player’s playtyle.There are process that must be carried out by a foreign citizen in order to obtain Indonesian citizenship status, and also those who have received citizeship status are guaranteed their rights and obligations by the state. Naturalization also involves several aspects such as constitutional, law, social dan political, cultural and economic. In its journey, the naturalization process carried out on the national team is supervised by Persatuan Sepakbola Seluruh Indonesia (PSSI) following the rules set by FIFA and naturalization regulations from Indonesian law, which is Undang - Undang Nomor 12 Tahun 2006 tentang Kewarganegaraan Republik Indonesia. It is hoped that the naturalization process carried out can obey the rules that have be set and not becoming an obstacle for the Indonesian national football team as a process that eliminates the identity of the national team.